2015
DOI: 10.1016/j.chembiol.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Host-Microbe Protein Interactions during Bacterial Infection

Abstract: Summary Interspecies protein-protein interactions are essential mediators of infection. While bacterial proteins required for host cell invasion and infection can be identified through bacterial mutant library screens, information about host target proteins and interspecies complex structures has been more difficult to acquire. Using an unbiased chemical cross-linking/mass spectrometry approach, we identified interspecies protein-protein interactions in human lung epithelial cells infected with Acinetobacter b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 85 publications
0
102
0
Order By: Relevance
“…Chemical cross-linking provides evidence of proximal solventaccessible sites on proteins in vivo and is a means to predict and assemble models of protein structures (34,35,39). It is important to note that the chemical cross-linking workflow in this study was performed on whole, functional mitochondria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical cross-linking provides evidence of proximal solventaccessible sites on proteins in vivo and is a means to predict and assemble models of protein structures (34,35,39). It is important to note that the chemical cross-linking workflow in this study was performed on whole, functional mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…Large-scale XL-MS offers two key benefits. First, in conjunction with in silico modeling of structures, the identification of cross-linked interactions enables the observation of the physical features of proteins, including membrane proteins (33,34). These capabilities can uncover novel functions derived from protein-protein interactions, and crosslinks have provided data complementary to cryo-EM and crystallography to enhance the understanding of the structure and function of complex systems (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular mention is outer membrane protein A (OmpA) which has been suggested to have a variety of functions, including adhesion to host epithelial cells, biofilm function, and complement resistance (100). In a recent lethal model of A. baumannii pneumonia, transposon-mediated disruption of OmpA reduced mortality in small numbers of mice, suggesting a virulence function of the OmpA (100).…”
Section: Acinetobacter Virulence Factorsmentioning
confidence: 99%
“…PIR-derived cross-linked sites identified between or within proteins are then used as distance constraints to develop structural models that enable visualization of proteins and protein complexes, as they exist in cells during cross-linker application (19,23,24). A recent study using in vivo PIR application confirmed OmpA homodimer existence and interfacial regions that were originally identified in bacterial cells by traditional MS methods (25), demonstrating the ability to derive meaningful structural information from this experimental approach.…”
mentioning
confidence: 80%